Similar Efficacy of Arthroscopy and Arthrotomy in Infection Eradication in the Treatment of Septic Knee: A Systematic Review and Meta-Analysis - Liang, Zhimin; Deng, Xiaofan; Li, Lingli; Wang, Jing (Frontiers in Surgery, 2022)
Aim To compare the arthroscopy versus arthrotomy for the treatment of native knee septic arthritis. Methods Electronic databases of PubMed, Embase and Cochrane Library were searched for eligible studies. Retrospective comparative studies comparing arthroscopy or arthrotomy for patients with septic arthritis of the native knee were eligible for this review. The primary outcome was recurrence of infection after first procedure. The secondary outcomes included hospital length of stay, operative time, range of motion of the involved knee after surgery, overall complications and mortality rate, Results Thirteen trials were included in this study. There were a total of 2162 septic arthritis knees treated with arthroscopic debridement and irrigation, and 1889 septic arthritis knees treated with open debridement and irrigation. Arthroscopy and arthrotomy management of the knee septic arthritis showed comparable rate of reinfection (OR = 0.85; 95% CI, 0.57 to 1.27; P = 0.44). No significant difference was observed in hospital length of stay, operative time and mortality rate between arthroscopy and arthrotomy management group, while arthroscopy treatment was associated with significantly higher knee range of motion and lower complication rate when compared with arthrotomy treatment. Conclusion Arthroscopy and arthrotomy showed similar efficacy in infection eradication in the treatment of native septic knee. However, arthroscopy treatment was associated with better postoperative functional recovery and lower complication rate.